Evaluasi Persepsi Mahasiswa atas Relevansi dan Kepraktisan E-Modul Ilmu Lingkungan Berbasis Kearifan Lokal Riau - Ermina Sari; Raudhah Awal; Martalasari (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
This study analyzed students' perceptions of an ethnoscience-integrated Environmental Science e-module, focusing on two dimensions: content relevance and usability. A mixed-methods approach with a descriptive-analytical design was employed. Quantitative data were collected using a Likert-scale perception questionnaire and complemented by qualitative data obtained through reflective interviews. The participants consisted of 32 undergraduate students from the Biology Education Study Program at Universitas Lancang Kuning who had directly used the e-module in Environmental Science learning. The findings indicated that the e-module achieved an excellent rating for content relevance (87.6%) and a good-to-excellent rating for usability (84.4%). Students perceived that the integration of Riau Malay local wisdom enhanced their conceptual understanding and strengthened the connection between course content and local environmental realities. Qualitative findings further revealed that culturally grounded content promoted greater learning engagement, ecological awareness, and affective reflection on environmental values. This study concludes that integrating ethnoscience into the Environmental Science e-module significantly contributes to fostering positive student perceptions regarding the relevance and usability of digital learning media. The findings also highlight its potential to strengthen environmental literacy within the frameworks of Outcome-Based Education (OBE) and the Merdeka Belajar–Kampus Merdeka (MBKM) policy.